Cultural And School Factors As Predictors Of Mathematics Teachers’ Use Of Information And Communication Technology (ICT) For Instruction In Ogun State - Olafare Festus Oladimeji; Boor Charity Mwuese; Taiwo Oyeladun Mary; Adeyanju Lawrence Olugbade (Universitas Negeri Makassar, 2019)
This study aims to find out if culture and school factors serve as predictors of mathematics teachers’ use of information and communication technology for instruction in secondary school. The sample for this study comprises 171 secondary schools’ teachers from 17 government-owned secondary schools in Ogun State, Nigeria. Data were collected through a questionnaire. The result shows that culture does not serve as a predictor of mathematics teachers’ use of ICT for teaching but school factors serve as a predictor of mathematics teachers’ use of ICT for teaching. It was also discovered that there was no significant relationship between culture and school factors as predictors of mathematics teachers’ use of ICT for teaching. Based on these findings, it was concluded that the obtainability of ICT facilities and other factors in school is important to mathematics teaching..